Electrical characteristics of photovoltaic cell module by simulation - Dolah, Asban (2015)
This paper emphasizes on the model verification of the electrical performance of a Photovoltaic (PV) cell module by MATLAB/Simulink simulation. The developed model can then be us ed to predict the PV cell behavior under different physical and environmental parameters such as solar irradiation, ambient temperature, series resistor, shunt resistor, diode saturation current and cell arrangement. Photovoltaic cell model is used for com par i ng the electrical characteristics for this modeling process. Kyocera PV module is used as the module specification, whereby a PV model can be easily generalized to predict the output current, power characteristics and the maximum power point tracking.